2018
DOI: 10.3389/fmicb.2018.02209
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Bile Salt Types Influence the Composition of Biliary Bile Acids and Gut Microbiota in Grass Carp

Abstract: Lipid metabolism can influence host’s health. There is increasing evidence for interplay between two key regulating factors in lipid metabolism: bile acids (BAs) and gut microbiota. However, very little is known about how types of different diet-supplemented bile salts (BS) influence this interaction in vivo. We sought to explore these relationships using grass carp (Ctenopharyngodon idellus), which often suffers functional disorder of liver and gallbladder. We studied fluctuations of BAs in the gall and chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 66 publications
(83 reference statements)
4
21
1
Order By: Relevance
“…As BA‐metabolizing bacteria, we also found that many of these differential OTUs belonged to Lachnospiraceae and Ruminococcaceae had a strong correlation with altered BAs in feces and serum, indicating that Ruminococcaceae and Lachnospiraceae were closely related to the biotransformation of BAs. Consistent with our findings, a previous study conducted in grass carp feeding different bile salt revealed that Lachnospiraceae and Ruminococcaceae were the bacterial taxa that most closely positively correlated with biliary BAs 51 . In agreement, antibiotics‐induced decrease of secondary BAs (DCA, LCA, UDCA, HDCA, and ω‐MCA) in mice were correlated with the loss of specific microbiota community members, such as the Lachnospiraceae and Ruminococcaceae families 52 .…”
Section: Discussionsupporting
confidence: 92%
“…As BA‐metabolizing bacteria, we also found that many of these differential OTUs belonged to Lachnospiraceae and Ruminococcaceae had a strong correlation with altered BAs in feces and serum, indicating that Ruminococcaceae and Lachnospiraceae were closely related to the biotransformation of BAs. Consistent with our findings, a previous study conducted in grass carp feeding different bile salt revealed that Lachnospiraceae and Ruminococcaceae were the bacterial taxa that most closely positively correlated with biliary BAs 51 . In agreement, antibiotics‐induced decrease of secondary BAs (DCA, LCA, UDCA, HDCA, and ω‐MCA) in mice were correlated with the loss of specific microbiota community members, such as the Lachnospiraceae and Ruminococcaceae families 52 .…”
Section: Discussionsupporting
confidence: 92%
“…Our findings indicated that dietary supplementation of bile acids induced marked alterations of functionality of intestinal microbiota in shrimp. Among them, consistent with previous investigations about grass carp (Xiong et al, 2018), the lipid metabolism capacity of intestinal microbiota in BA2 and BA4 groups increased, further confirming that bile acids were significant to the emulsification of lipid and the metabolism of shrimp. Meanwhile, functional genes associated with metabolism (including amino acid, energy, nucleotide, cofactors and vitamins) were all increased after dietary supplementation of bile acids.…”
Section: Discussionsupporting
confidence: 91%
“…The PCR was conducted using the bacterial universal primers 338F (5′ ACT CCT ACG GGA GGC AGC AG 3′) and 806R (5′ GGA CTA CHV GGG TWT CTA AT 3′). The PCR reaction was based on Xiong et al (43). The resulted PCR products were extracted from a 2% agarose gel and further purified using the AxyPrep DNA Gel Extraction Kit (Axygen Biosciences, Union City, CA, USA) and quantified using QuantiFluor™ -ST (Promega, USA) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%